Treatment outcomes of bedaquiline-based longer oral antitubercular regimens in Indian children above five years of age - Ira Shah; Dhruv N. Gandhi; Ramsha Ansari; Himanshu Warse; Sachi Kalawadia; Tsering Yangchen; Daksha Shah; Varsha Puri; Sanjay Mattoo; Minnie Bodhanwala (Lung India)
Background and Objective: This study evaluates the treatment outcomes and adverse drug reactions (ADRs) of longer oral bedaquiline (BDQ)-based (without delamanid) antitubercular therapy (ATT) regimens in children aged 5–18 years. Methods: A retrospective study was conducted between June 2021 and February 2024. We included 105 children diagnosed with drug-resistant tuberculosis (DR-TB) and treated with longer oral BDQ-based regimens. Duration of treatment was based on clinico-radiological resolution and multiple ADRs. Data on demographics, clinical features, resistance patterns, treatment regimens, outcomes, and adverse effects were analyzed. Results: Mean age was 11.29 ± 3.20 years, with a male-to-female ratio of 0.42:1. Prior ATT exposure was reported in 61 (58.1%), with previous treatment failure in 34 (55.7% of those with prior exposure) patients. BDQ was administered for a median duration of 6 months, with 14 (13.33%) requiring extension. BMLCC (bedaquiline–moxifloxacin–linezolid–cycloserine–clofazimine) regimen was received by 61 (58.1%), and BLCC ± additional drugs (bedaquiline–linezolid–clofazimine–cycloserine) regimen was received by 30 (28.6%) patients. Treatment completion was achieved in 75 (71.43%) patients with a mean duration of 22.50 ± 7.50 months, of which 35 (46.67%) required treatment for 18 months, 32 (42.67%) required treatment for more than 18 months, and 8 (10.67%) patients required treatment stoppage before 18 months in view of multiple ADRs. Fifty-one (48.6%) patients had ADRs, including QTc prolongation in 25 (23.8%), psychosis 11 (10.5%), and vomiting 7 (6.7%). Conclusion: BDQ-based regimens are effective in treating pediatric DR-TB, with high treatment completion rates. However, the duration of treatment is 18 months or longer in most patients based on clinico-radiological resolution. ADRs, particularly QTcF prolongation, warrant close monitoring and follow-up.